1988
DOI: 10.2190/qpew-n6qx-fwde-la7e
|View full text |Cite
|
Sign up to set email alerts
|

Indoor and Outdoor Activities of Aged Women and Men as Related to Depression and Well-Being

Abstract: This article examines the relations between reported level of activity and measures of affect in old people exploring possible sex differences. It was hypothesized that these relations are mediated by the satisfaction from the specific activity. The sample consisted of fifty-four women and forty-five men, ranging in age from sixty to eighty, functioning normally in the community. A questionnaire assessed participants' levels of indoor/outdoor activities. Participants rated their satisfaction for each of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 25 publications
0
26
0
2
Order By: Relevance
“…The maintenance of physical and social activities likely serves as an important buffer against the negative effects that often accompany illness. Physical activity has been shown to improve mood, wellbeing, and self-efficacy, and social activities have been linked to the absence of depression (Strawbridge, Cohen, Sherma, & George, 1996), increased longevity (Berkman & Syme, 1979), and positive well-being (Lomranz, Bergman, Eyal, & Shmotkin, 1988;Mancini, 1978;Reich & Zautra, 1981;Russell, 1990;Steinkamp & Kelly, 1987;Zimmer et al, 1995). The role of physical and social activities in maintaining positive well-being during illness episodes has not been explored in prospective studies.…”
Section: Hypothesesmentioning
confidence: 99%
“…The maintenance of physical and social activities likely serves as an important buffer against the negative effects that often accompany illness. Physical activity has been shown to improve mood, wellbeing, and self-efficacy, and social activities have been linked to the absence of depression (Strawbridge, Cohen, Sherma, & George, 1996), increased longevity (Berkman & Syme, 1979), and positive well-being (Lomranz, Bergman, Eyal, & Shmotkin, 1988;Mancini, 1978;Reich & Zautra, 1981;Russell, 1990;Steinkamp & Kelly, 1987;Zimmer et al, 1995). The role of physical and social activities in maintaining positive well-being during illness episodes has not been explored in prospective studies.…”
Section: Hypothesesmentioning
confidence: 99%
“…The other two studies reporting differential effects for sex were not exercise training studies but rather survey/recall studies (Lomranz, Bergman, Eyal, & Shmotkin, 1988;Morgan et al, 1991). The Morgan et al (1991) study reported only a weak relationship between customary physical activity over the previous 6 weeks and PWB for men, and no relationship for women.…”
Section: Does Physical Activity Influence Psychological Well-being?mentioning
confidence: 99%
“…The Morgan et al (1991) study reported only a weak relationship between customary physical activity over the previous 6 weeks and PWB for men, and no relationship for women. Lomranz et al (1988) reported the relationship between participation in indoor and outdoor activities over the past week and well-being in older adults. Results for affect balance scores suggest that activity is related to positive affect in males more than in females.…”
Section: Does Physical Activity Influence Psychological Well-being?mentioning
confidence: 99%
“…For example, Keith (1980) noted that men gain more from outdoor and maintenance activities while women more likely benefit from social pursuits. Lomranz, Bergman, Eyal & Shmotkin (1988), found that although elderly men benefit from both outdoor and indoor recreation, among women, positive influences are found for indoor activities only. In looking at compulsory physical activity, Morgan et al (1991) found that only men profited emotionally from increased participation.…”
Section: Development Of Hypothesesmentioning
confidence: 99%